Meteorological parameters as an important factor on the energy recovery of landfill gas in landfills - Uyanik, Ibrahim; Ozkaya, Bestamin; Demir, Selami; Cakmakci, Mehmet (AMER INST PHYSICS, 2012)
The effect of meteorological factors on the composition and the energy recovery of the landfill gas (LFG) were evaluated in this study. Landfill gas data consisting of methane, carbon dioxide, and oxygen content as well as LFG temperature were collected from April 2009 to March 2010 along with meteorological data. The data set were, first, used to visualize the similarity by using self-organizing maps and to calculate correlation factors. Then, the data was used with ANN to further analyze the impacts of meteorological factors. In both analysis, it is seen that the most important meteorological parameter effective on LFG energy content is soil temperatures. Furthermore, ANN was found to be successful in explaining variations of methane content and temperature of LFG with correlation coefficients of 0.706 and 0.984, respectively. ANN was proved itself to be a useful tool for estimating energy recovery of the landfill gas. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4769202]
Keywords: SOLID-WASTE LANDFILL; METHANE OXIDATION; ATMOSPHERIC-PRESSURE; SANITARY LANDFILLS; POWER-GENERATION; EMISSIONS; SITE; TEMPERATURE; MIGRATION; SOIL; Science & Technology - Other Topics; Energy & Fuels